The concept of motherhood in the Bible = Ha-Imahut ba-Mikra - Reisenberger, Azila Talit (Kaplan Centre for Jewish Studies, 2017)
Following the canonization of the Hebrew Bible, a new process of interpreting this text was initiated. Despite the vast amount of biblical research generated in the two thousand years since the canonization, relatively little has been written on the subject of "Womanhood" in the Bible. With the change in the status of women in modern times, a growing interest has emerged in their counterpart, namely, the women in Ancient Israel. The concept of "Motherhood", which was seen as the imperative of woman's existence has, like other aspects of the woman's life, been researched from legal, medical, social and other points of view. The ensuing work investigates the influence that motherliness and the concept of Motherhood as a whole has had on the culture recorded in the Hebrew Bible. Three main areas are explored in this study, namely: 1. Literary Conventions 2. Rhetorical Strategies, and 3. Linguistic Developments. Each of these respectively constitutes a sub-section of the study. The first section is composed of two chapters. Chapter one traces those biblical stories which follow the theme of the barren woman who gives birth to a hero. Chapter two in turn deals with the theme of women who bear children easily, and the consequent fate that awaits them. The second section investigates the rhetorical strategies employed in two respective Biblical themes, which were used to foretell, in a pseudo-prophetic manner, and thereby to excuse and justify certain events which were to follow in the course of history. The first chapter deals with the narrative which depicts a woman who takes an unusual initiative in her attempts to fulfil her desire to become a mother. The second chapter examines the initial reactions of mothers to their new born offspring and how this in turn influences their later status in the family. Analysis of the rhetorical strategies employed in both cases, sheds light on the views on "Motherhood" held by the biblical author, and his approval or disapproval of national leaders, at the time of their birth. The third section is comprised of two chapters. In the first chapter a correlation is drawn between language and cultural development. In the second chapter all words, new roots and idioms which have evolved out of the various aspects of "Motherhood" are categorised. The author concludes that a vast impact of the concept of Motherhood is evident in the biblical language, the rhetorical techniques and the literary conventions which form the context within which religious beliefs are formed and historical events are recorded. It is the author's contention that an understanding of this influence will lead to a greater comprehension of the Hebrew Bible and the message carried within it, and will facilitate a theological study of the influence of "Motherhood", on the development and understanding of the abstract concept of monotheism. The Language employed in the investigation is Hebrew